FRAMEWORK STUDI MAQASHID AL-SYARI’AH; ANTARA PENALARAN TEKSTUAL DAN KONTEKSTUAL - Sahidin, Amir (DAS Institute, 2022)
This article starts from misunderstanding of some Muslims in reasoning maqashid al-syari'ah. Some of them argue that maqashid al-syari'ah is only what appears of the text to nash, so they reason the text textually. As a result, Islamic law becomes rigid and it is easy to blame you. Some of them reasoned too much about maqashid al-syari'ah, thus canceling the text of the nash. As a result, he was brave enough to deconstruct a permanent Islamic law. Therefore, this article will examine maqashid al-syari'ah with a fair and moderate study (wasathiyah) that is not as extreme as textual or contextual reasoning. Through a critical analysis study of various authoritative literature, it was found that, first: wasathiyah reasoning in maqashid al-syari'ah reasoning is to distinguish between worship and muamalat matters in terms of the intentions behind them; second: looking for maqashid al-shari'ah before determining the law; third: principled that the shari'a which is built on the qath'i argument will not conflict with benefit and common sense.